Chemical content in the sembeq traditional rituals of the Lombok Community - Yayuk Andayani; Burhanuddin Burhanuddin; Aliefman Hakim; I Nyoman Loka; MutiÃ¢â¬â¢ah MutiÃ¢â¬â¢ah (Jurnal Pijar Mipa, 2021)
This study aims to identify and describe the chemical content in the sembeq traditional rituals, especially in the medicinal purpose of the Lombok community. Qualitative approach research with a phenomenological approach is used in focusing on data collecting of the Sembeq tradition. Data on indigenous knowledge of the community was obtained through interviews with Belians, who were the key informants. Data in the form of narration were analyzed descriptively. The results showed that in the Sembeq tradition, which is used for medicinal purposes, the main ingredients are betel leaf, areca nut, and fine lime. Chemical content relevant to the sembeq tradition includes secondary metabolites, mixtures, chemical reactions, bases, solution pH, and surface area.